2023
DOI: 10.18063/ijb.737
|View full text |Cite
|
Sign up to set email alerts
|

Research landscape of 3D printing in bone regeneration and bone repair: A bibliometric and visualized analysis from 2012 to 2022

Abstract: Three-dimensional printing (3DP) is a popular manufacturing technique with versatile potential for materials processing in tissue engineering and regenerative medicine. In particular, the repair and regeneration of significant bone defects remain as substantial clinical challenges that require biomaterial implants to maintain mechanical strength and porosity, which may be realized using 3DP. The rapid progress in 3DP development in the past decade warrants a bibliometric analysis to gain insights into its appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…It is now widely used in medical fields, such as orthopedics, autoimmune diseases, etc. [ 15 17 ] However, no bibliometric studies on wrist arthroscopy have been found in recent years. Therefore, in this study, we utilized sophisticated bibliometric tools, including CiteSpace, [ 18 ] VOSviewer, [ 19 ] R package“Bibliometrix,” [ 20 ] and an online analysis platform ( https://bibliometric.com ), to obtain comprehensive data on references related to wrist arthroscopy literature.…”
Section: Introductionmentioning
confidence: 99%
“…It is now widely used in medical fields, such as orthopedics, autoimmune diseases, etc. [ 15 17 ] However, no bibliometric studies on wrist arthroscopy have been found in recent years. Therefore, in this study, we utilized sophisticated bibliometric tools, including CiteSpace, [ 18 ] VOSviewer, [ 19 ] R package“Bibliometrix,” [ 20 ] and an online analysis platform ( https://bibliometric.com ), to obtain comprehensive data on references related to wrist arthroscopy literature.…”
Section: Introductionmentioning
confidence: 99%